Learning strategies in the communication area organizational climate and teaching performance at the “Túpac Amaru” educational institution. Villa María del Triunfo, Lima - 2014. - López Catalán, Marilina (2021)
At the “Túpac Amaru” school. Villa María del Triunfo, Lima 2014, we carried out a scientific study with a quantitative approach, posing the hypothesis that the organizational climate is related to teaching performance. The population and sample consisted of 4 directors and 89 teachers from the Túpac Amaru school. We used the survey technique and the structured questionnaire instrument, an observation sheet, which met the qualities of validity and reliability. The research design is transectional, correlational, causal, bivariate, cross-sectional. For data collection, two structured questionnaires were made as measurement, also an observation sheet, interview with the students. We analyze the organizational climate variable from the managerial style, leadership, levels of communication, conflict management and the teacher performance variable from; methodological strategies, teaching planning, use of educational media and materials, professional solvency. The sample consisted of 4 directors and 89 teachers from the “Túpac Amaru” Educational Institution. Villa Maria del Triunfo, Lima 2014. Our results allow us to reject the null hypothesis and accept the investigated hypothesis since it has been found according to the Spearman Rho correlation of 0.538 is a MODERATE association of the variables and being highly significant. In addition, according to the highly significant independence tests (*** p <.000), the research hypothesis is accepted: There is a direct and significant relationship between Organizational Climate and Teaching Performance in the Educational Institution “Túpac Amaru”. Villa Maria del Triunfo, Lima 2014